2021
DOI: 10.5603/aa.2021.0003
|View full text |Cite
|
Sign up to set email alerts
|

Primary Patency Rates of Endovascular Interventions in Hemodialysis Patients with Central Venous Stenosis and Occlusions

Abstract: Introduction:The purpose of this study was to determine the primary patency rate of endovascular interventions in hemodialysis patients who had central venous stenosis or occlusion. Material and methods: Twenty-seven hemodialysis patients, who underwent endovascular intervention between January 2013 and January 2018 for central venous stenosis or total obstruction, were included in the study. Endovascular interventions consisted of percutaneous transluminal angioplasty (PTA) or stent implantation. Primary pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…The analysis of the causes of death showed that the causes of cardiovascular disease accounted for 46.67%, ranking first, followed by the cause of infection, accounting for 22.22%. Cardiovascular disease is the first cause of death, which is in line with the results of several domestic studies [3][4][5]7]. This study [8] showed that the risk of death from cardiovascular disease was 10 to 20 times higher than that of the general population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The analysis of the causes of death showed that the causes of cardiovascular disease accounted for 46.67%, ranking first, followed by the cause of infection, accounting for 22.22%. Cardiovascular disease is the first cause of death, which is in line with the results of several domestic studies [3][4][5]7]. This study [8] showed that the risk of death from cardiovascular disease was 10 to 20 times higher than that of the general population.…”
Section: Discussionsupporting
confidence: 83%
“…The mean time from hemodialysis start to death of the 45 deceased patients included in this study was (9.04 ± 2.16) months, which is similar to the results of several centers in the country [3][4][5]. 45 cases in the central disease is diabetic nephropathy (42.22%), followed by hypertensive renal damage (28.89%), chronic glomerulonephritis (13.33%), which suggests that diabetic nephropathy is the primary cause of elderly patients with end-stage renal disease, analysis may be related to the domestic elderly population diabetes higher than young people (55.56% of patients in this group for diabetic nephropathy or nephropathy with diabetes), and diabetic nephropathy patients with cardiovascular and other complications earlier and earlier into hemodialysis treatment [6].…”
Section: Discussionsupporting
confidence: 79%
“…Purified blood is then transfused back. [6,7] Although hemodialysis can effectively prolong the life of patients, MH can have a significant impact on their physical and mental health. In long-term treatment, it not only causes great pain to the patient’s body, but also increases the burden on the family.…”
Section: Introductionmentioning
confidence: 99%